2000
DOI: 10.1111/j.1651-2227.2000.tb00084.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of nebulized surfactant therapy for neonatal respiratory distress syndrome

Abstract: Thirty-four spontaneously breathing newborns with respiratory distress syndrome (RDS) requiring nasal continuous positive airway pressure (CPAP) and an arterial-to-alveolar oxygen tension ratio (a/A PO2) of 0.15-0.22 were randomized to treatment with nebulized surfactant (Curosurf) or to serve as controls. All children were first supported by nasal CPAP according to normal clinical routines. Surfactant was administered using a modified Aiolos nebulizer, and a total of 480 mg was aerosolized in each case. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(46 citation statements)
references
References 20 publications
0
42
0
4
Order By: Relevance
“…Surfactant replacement therapy by nebulization during non-invasive ventilation represents a truly non-invasive surfactant administration method, which, unfortunately, remains an unfulfilled goal of modern neonatal care. Several clinical studies have demonstrated the safety of nebulized surfactant in combination with continuous positive pressure ventilation (CPAP) [7][8][9][10][11]. Recently, Minocchieri et al have demonstrated that Poractant alfa nebulized with a vibrating-membrane nebulizer reduces the need for intubation in 32 0 -33 6 weeks gestational age (GA) infants with mild RDS, although no differences were observed in 29 0 -31 6 weeks GA babies [11].…”
Section: Introductionmentioning
confidence: 99%
“…Surfactant replacement therapy by nebulization during non-invasive ventilation represents a truly non-invasive surfactant administration method, which, unfortunately, remains an unfulfilled goal of modern neonatal care. Several clinical studies have demonstrated the safety of nebulized surfactant in combination with continuous positive pressure ventilation (CPAP) [7][8][9][10][11]. Recently, Minocchieri et al have demonstrated that Poractant alfa nebulized with a vibrating-membrane nebulizer reduces the need for intubation in 32 0 -33 6 weeks gestational age (GA) infants with mild RDS, although no differences were observed in 29 0 -31 6 weeks GA babies [11].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of nCPAP and aerosolized surfactant has been explored in small pilot studies in premature infants with clinical (animal-derived) lung surfactants and first generation synthetic surfactants (Exosurf Neonatal ® and Surfaxin ® ) (Jorch et al, 1997 [Alveofact ® ]; Arroe et al, 1998 [Exosurf Neonatal ® ]; Berggren et al, 2000 [Curosurf ® ]; Finer et al, 2010 [Surfaxin ® ]), but these studies did not provide good data on clinical efficacy, aerosol generation and nCPAP, and particle size in lung deposition (Pillow & Minocchieri, 2012). As a result, a recent Cochrane Systematic Review concluded that there are insufficient data to support or refute the use of nebulized surfactant in clinical practice (Abdel-Latif & Osborn, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For this method to be effective, aerosolized particles of surfactant ranging from 1 to 5 μm in diameter must be delivered to the lungs in a predictable and reproducible fashion. Many different surfactant preparations and nebulizers have been developed and tested in small trials [20, 21]. However, the optimal combination and dosages have yet to be determined.…”
Section: Less Invasive Surfactant Administration Techniquesmentioning
confidence: 99%